Association of GATA3 Polymorphisms With Minimal Residual Disease and Relapse Risk in Childhood Acute Lymphoblastic Leukemia. (7th September 2020) - Zhang, Hui; Liu, Anthony Pak-Yin; Devidas, Meenakshi; Lee, Shawn HR; Cao, Xueyuan; Pei, Deqing; Borowitz, Michael; Wood, Brent; Gastier-Foster, Julie M; Dai, Yunfeng; Raetz, Elizabeth; Larsen, Eric; et al.
Abstract: Background: Minimal residual disease (MRD) after induction therapy is one of the strongest prognostic factors in childhood acute lymphoblastic leukemia (ALL), and MRD-directed treatment intensification improves survival. Little is known about the effects of inherited genetic variants on interpatient variability in MRD. Methods: A genome-wide association study was performed on 2597 children on the Children's Oncology Group AALL0232 trial for high-risk B-cell ALL. Association between genotype and end-of-induction MRD levels was evaluated for 863 370 single nucleotide polymorphisms (SNPs), adjusting for genetic ancestry and treatment strata. Top variants were further evaluated in a validation cohort of 491 patients from the Children's Oncology Group P9905 and 6 ALL trials. The independent prognostic value of single nucleotide polymorphisms was determined in multivariable analyses. All statistical tests were 2-sided. Results: In the discovery genome-wide association study, we identified a genome-wide significant association at the GATA3 locus (rs3824662, odds ratio [OR] = 1.58, 95% confidence interval [CI] = 1.35 to 1.84; P = 1.15 × 10 -8 as a dichotomous variable). This association was replicated in the validation cohort ( P = .003, MRD as a dichotomous variable). The rs3824662 risk allele independently predicted ALL relapse after adjusting for age, white blood cell count, and leukemia DNA index ( P = .04 and .007 in the discovery and validation cohort, respectively) and remained prognostic when the analyses were restricted to MRD-negative patients ( P = .04 and .03 for the discovery and validation cohorts, respectively). Conclusion: Inherited GATA3 variant rs3824662 strongly influences ALL response to remission induction therapy and is associated with relapse. This work highlights the potential utility of germline variants in upfront risk stratification in ALL.